Effect of different folltropin doses in buffaloes - PAWSHE, C H; SAHATPURE, S K; PATIL, M S; DESHMUKH, S G; RAZZAQUE, W A A; GAWANDE, A P; FASIHUDDIN, M; PATIL, R K (The Indian Journal of Animal Sciences, 2014)
Cyclic buffaloes (29) were divided randomly in to 3 different groups for superovulatory treatment with different dose regimen of folltropin -V. Group 1 (8) buffaloes were treated with 450 mg folltropin -V; group 2 (13) buffaloes were treated with 500 mg folltropin -V, and group 3(8) buffaloes were treated with 560 mg follotropin-V. All the animals (100%) responded to the treatment. The average time required for onset of oestrus was 31.88 ± 2.35 hr, 28.46 ± 0.28 hr and 28.00 ± 3.41 hr and the duration of super ovulatory oestrus was 25.63 ± 1.80 hr, 34.00 ± 2.79 hr and 31.38 ± 3.26 hr in group 1, group 2 and group 3 respectively. The average number of corpora lutea and unovulatory follicles were 4.13 ± 0.74 and 1.38 ± 0.56; 3.46 ± 0.39 and 0.77 ± 0.17; 3.88 ± 0.61 and 1.13 ± 0.30 in groups 1,2 and 3 respectively. Total 7 transferable embryos were recovered - one from group 1 and 6 from group 2, however, no embryo was recovered from group 3.